Teori Harga Islami Pandangan Kritis Terhadap Konsep Harga Kapitalis - Cahyadi, Thalis Noor (Universitas Alma Ata, 2009)
According to M. Abdul Mannan in his book Islamic Economics, Theory and Practice, especially in Chapter VIII describes about how to realize the Islamic price totally with emphasis on the aspect of needs (needs) to human and human resource. Mannan also describes how to create an Islamic market and an ideal industrial which related between producers and consumers, including the labor which is then connected to the various factors that influence the price increase.Mannan price classifies into four forms namely the monopoly price, actual price increases, price increases imitation, and the price increases caused by the necessities of life. Mannan provide advice in the form of establishment Wilayatul-hisba or supervisory agency prices, while on the other hand the need for the establishment of consumer associations who have a bargaining position against the manufacturer, in addition dialogue method in case of problems between them. The government also felt necessary to make the regulation and supervision of prices that not harm consumers and society.Keywords: ijtihad, price Islami, Islami work patterns, the dialogue.